Pemberian Edukasi pada Pasien Pasca SC untuk Menurunkan Kecemasan - Fransi Arsani; Ahmad Zainullah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Post-Cesarean Section (CS) patients often experience anxiety that can hinder the recovery process. Limited time for health workers to provide comprehensive education is one of the main factors causing a lack of patient understanding of post-CS care. This study aims to evaluate the effectiveness of providing video-based education and interactive sessions in reducing anxiety in post-CS patients. The methods used include socialization, video-based training, direct practice, and evaluation through pre-test and post-test questionnaires. The results showed an increase in patient understanding and compliance with post-CS care and a significant decrease in anxiety levels. Video-based education has been shown to be effective in helping patients understand recovery procedures better and reducing dependence on analgesics. Therefore, the implementation of similar education methods is recommended in health services to improve the quality of recovery in post-CS patients